Fala Preta!: mulheres negras no espaço urbano - origem e memória -1997 a 2007 - Carlos, Elza da Silva (2009)
In the 1980 s, there developed a feminist movement of black women that where drawn and organized from various backgrounds and communities. These organizations developed into the creation of new political organizations of workingclass Black Women, leading in 1997 to the Fala Preta! NGO Black Women Organization. This is a study about the militant group Fala Preta! and how it has organized black women between the period of 1997 to 2007. During this study I have undertaken interviews with managers, who formed part of the selected projects and I have researched the historical documents and writings the organization. It contributes to the history of black women, and emphasizes how they suffered from discrimination of gender, race and social class within Brazilian society